Freedom of expression as self-restraint - Kramer, Matthew H. 1959- (Oxford University Press, 2021)
Freedom of Expression as Self-Restraint provides a novel justificatory foundation for the principle of freedom of expression. As the book argues, such a principle is absolute in that it is exceptionless; it imposes general duties that are binding always and everywere on every system of governance.0In addition to injecting a new level of philosophical sophistication into the debates over freedom of expression, the book ties the principle to an ideal of governmental self-restraint, and it shows how that ideal connects to the paramount moral responsibility of every system of governance: the responsibility to bring about the political, social, and economic conditions under which every member of society can be warranted in harbouring an ample sense of self-respect. In short, compliance by a system of governance with the principle of freedom of expression is integral to the fulfilment of that paramount responsibility.